Solvent engineering approach via introducing poly (3, 4-ethylene dioxy-thiophene)–poly (styrene sulfonate) (PEDOT:PSS) into photosensitive absorber layer for ambient temperature processed efficient inverted planar perovskite solar cells - Sagar Jain (Solar Energy, 2018)
The quality of photosensitive absorber layer plays an important role in the performance of organic-inorganic hybrid perovskite solar cells (PSCs). Here, for the first time a classic hole transport material, poly (3, 4-ethylene dioxy-thiophene)-poly (styrene sulfonate) (abbreviated as PEDOT:PSS) was introduced as additive directly into the CH3NH3PbI3−xClx perovskite absorber. On controlled fine-tuning of PEDOT:PSS concentration within perovskite resulted into the high-quality films with large crystal grains that ultimately resulted into improved optoelectronic and charge transport properties. Due to the complexation between the PEDOT:PSS and CH3NH3PbI3−xClx the defects in the active layer of perovskite as well as the passivation of back-and-front contact recombination occurred that leads to possible trap state healing in bulk as well at interfaces and this resulted into a longer lifetime charge carrier compare to the perovskite film without PEDOT:PSS additives. Solar cells prepared using 1.5 v% PEDOT:PSS and perovskite resulted an improved power conversion efficiency (PCE) of 17.56%. This finding provided a simple way to fabricate efficient planar perovskite solar cells for the commercial applications.